Effectiveness of D-RaCe, SP1 and R-Endo Rotary Systems for Root Canal Filling Material Removal from the Human Mandibular Molars: A Micro-CT Study - P Beikian Ghavidel; AA Moshari; S Toursavadkouhi (Islamic Azad University, 2023)
Background and Aim: The present study compared the retreatment efficacy of D-RaCe, SP1, and R-Endo rotary files in gutta-percha removal from the mesiobuccal canal of mandibular molars by micro-computed tomography (micro-CT).    Materials and Methods: In this experimental in vitro study, 30 mandibular molars were prepared with Denco-D-Super files and filled using gutta-percha and AH Plus sealer by the lateral compaction technique. Root canals then underwent micro-CT, and the amount of root filling material was measured on images using LOTUS InVivo-REC software. The teeth were randomly assigned to three groups (n=10) for retreatment with D-RaCe, SP1, and R-Endo systems. They underwent micro-CT again after retreatment, and the volume of residual root filling material in the root canals was calculated. The percentage of cleaning efficiency of each system in removal of gutta-percha from the mesiobuccal canal was calculated and compared among the three groups by two-way ANOVA and Tukey's test (alpha=0.05). Results: File type (P=0.05) and root canal region (apical, middle, or coronal third) (P<0.001) had significant effects on the percentage of cleaning efficiency. SP1 was significantly superior to R-Endo regarding cleaning efficiency (P=0.04). D-RaCe had the highest cleaning efficiency in the apical third (85.12%) while SP1 had the highest cleaning efficiency in the middle (91.57%) and coronal (68.22%) thirds. R-Endo had the lowest cleaning efficiency in the entire root canal system. Conclusion: Although none of the systems had 100% cleaning efficiency, the cleaning efficiency of D-RaCe and SP1 was superior to R-Endo for retreatment of mesiobuccal canal of mandibular molars.